MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN EDUKATIF BALOK ANGKA ADAPTIF KELOMPOK A KB AL AMIN 2 - Masruroh, Siti; Trianggono, Mochammad Maulana; Sugiarto, Muhammad Agus (Dharmas Education Journal (DE_Journal), 2024)
Most children have not been able to understand number symbols, children still feel confused when asked to show the number symbols. As for other factors, The educational resources that instructors frequently utilize are whiteboards, picture / poster media and explaining to children only verbally so that students feel bored and uninterested. The purpose of this study is to improve the ability to recognize numbers 1-10 in children aged 3-4 years through educational games of even semester playgroup number blocks at KB AL AMIN 2 Karang Semanding. number blocks are one of the visual media made of square wood consisting of 10 block units with different colors and numbers each block represents the number 1 block. While adaptive shaped embossed like braille. Class action research (PTK) is this research methodology. Six boys and ten girls made up the 16 children that participated in this study. In this study, documentation and observation were the methods used to acquire data. The study included quantitative-descriptive analysis methodologies to test the classical completeness of children's number recognition skills, ranging from 1 to 10. The findings demonstrated that learning activities using Adaptive Number Blocks media improved children's recognition of numbers 1–10. Specifically, in the pre-cycle, children's classical completeness in recognizing numbers 1–10 was only 37.5%; in cycle 1, it remained at 37.5%; and in cycle 2, it increased to 100%.